The Drosophila mus101 gene, which links DNA repair, replication and condensation of heterochromatin in mitosis, encodes a protein with seven BRCA1 C-terminus domains. - Yamamoto, R.R.; Axton, J.M.; Yamamoto, Y.; Saunders, R.D.; Glover, D.M.; Henderson, D.S. (Genetics, 2000)
The mutagen-sensitive-101 (mus101) gene of Drosophila melanogaster was first identified 25 years ago through mutations conferring larval hypersensitivity to DNA-damaging agents. Other alleles of mus101 causing different phenotypes were later isolated: a female sterile allele results in a defect in a tissue-specific form of DNA synthesis (chorion gene amplification) and lethal alleles cause mitotic chromosome instability that can be observed genetically and cytologically. The latter phenotype presents as a striking failure of mitotic chromosomes of larval neuroblasts to undergo condensation of pericentric heterochromatic regions, as we show for a newly described mutant carrying lethal allele mus101(lcd). To gain further insight into the function of the Mus101 protein we have molecularly cloned the gene using a positional cloning strategy. We report here that mus101 encodes a member of the BRCT (BRCA1 C terminus) domain superfamily of proteins implicated in DNA repair and cell cycle checkpoint control. Mus101, which contains seven BRCT domains distributed throughout its length, is most similar to human TopBP1, a protein identified through its in vitro association with DNA topoisomerase IIbeta. Mus101 also shares sequence similarity with the fission yeast Rad4/Cut5 protein required for repair, replication, and checkpoint control, suggesting that the two proteins may be functional homologs.